Pesan dakwah di Akun TikTok Aab Elkarimi: Analisis Semiotika Charles Sanders Peirce - Muhammad Aulia Firman; Chairiawaty; Parihat Kamil (Bandung Conference Series: Islamic Broadcast Communication, 2023)
Abstract. This research is motivated by the development of social media as a means of preaching and to understand what da'wah messages are contained in the Tiktok video "Aab Elkairmi". This has prompted researchers to conduct research on Aab Elkarimi's Tiktok content which contains da'wah content related to social, political, and religious issues. This research is a qualitative research with a descriptive approach, and uses a semiotic method. Charles Sanders Peirce semiotics is the semiotics used in this research. With the semiotic analysis of Charles Sanders Peirce researchers can find out the da'wah messages contained in the Tiktok account "Aab Elkarimi". As a result, the researchers found that in the short videos entitled "Mubadzir Pangan", "Monsterisasi Tauhid", "FWB", "Sesajen", "DSAS", the videos contain several elements of da'wah messages, namely: Aqidah Messages, Moral Messages, and Messages Sharia. Abstrak. Penelitian ini dilatarbelakangi oleh perkembangan media sosial sebagai sara dalam berdakwah dan untuk memahami pesan dakwah apa saja yang terkandung didalam video Tiktok “Aab Elkairmi”. Hal inilah yang mendorong peneliti untuk melakukan penelitian mengenai konten Tiktok Aab Elkarimi yang berisikan konten dakwah yang berkaitan dengan isu sosial, politik, dan agama. Penelitian ini merupakan penelitian kualitatif dengan jenis pendekatan deskriptif, dan menggunakan metode semiotika. Semiotika “Charles Sanders Peirce” adalah semiotika yang digunakan pada penelitian ini. Dengan analisis semiotika “Charles Sanders Peirce” peneliti dapat mengetahui pesan-pesan dakwah yang terdapat di akun Tiktok “Aab Elkarimi”. Hasilnya peneliti menemukan bahwa di dalam video pendek berjudul “Mubadzir Pangan”, “ Monsterisasi Tauhid”, “FWB”, ”Sesajen”, “DSAS”, video-video tersebut mengandung beberapa unsur pesan dakwah yakni: Pesan Aqidah, Pesan Akhlak, dan Pesan Syariah.